Evaluation of onion cultivars in agroecological production system in the municipality of Glória de Dourados, MS (Research, Society and Development, 2022)
The aim of this work was to evaluate the productive capacity and adaptability of different cultivars of onion, in agroecological bases, in the edaphoclimatic conditions of the region of Grande Dourados, MS. The experiment was carried out in a Red Argisol, with a sandy texture. The experimental design was randomized blocks, with ten treatments for open-pollinated onion cultivars. The cultivars responded differently to agroecological cultivation in the edaphoclimatic conditions of the region. Vale Ouro IPA-11 and Red Creole had the highest plant heights, with 15.4 and 14.1 cm, respectively. All cultivars reached a transversal diameter of the bulb (63 to 74 mm) considered ideal for commercialization. The cultivars Texas Grano 502 (34 t ha-1), Crioula (34.4 t ha-1) and Vale Ouro - IPA 11 (34.9 ha-1) showed greater adaptability to cultivation on agroecological bases and high productive capacity in conditions to which they were submitted, reaching an average of productivity above the national average. These results can help in the choice of cultivars most adapted to the soil and climate conditions of the Grande Dourados-MS region, as well as to cultivation on agroecological bases, thus causing socioeconomic and environmental impacts and becoming a production alternative for family farmers in the region.